(3cJGH aj GdHGWfjIs
(3ChdgG (B:s
(3GdMeO ddg GdehMO HbOQJg ddeHOYGJ GdTGed HYfGjJg ddeLJQYGJ hGdechfGJ hGdeNdhbGJ s
(3BNQgG (B:s
(3CHdZ dPdc Hfj GdYHGS eGdcg JeJ hGdMeO ddg hMOg hUdhGJg Ydi eMeO GdfHj hBdg hSde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(G 3) s
Keywords: (3GdJhMjO hGdedd hGdfMds